THU0200 Clinical and radiological characteristics of interstitial lung disease in japanese patients with microscopic polyangiitis. (23rd January 2014) - Maeda, A.; Yamada, H.; Yamasaki, Y.; Shibata, T.; Nagafuchi, H.; Kurihara, Y.; Ozaki, S.
Abstract : Background: The anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitides such as granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with poliangiitis (EGPA) frequently involve multiple internal organs including lung diseases, which affect their survival. Among lung involvements, interstitial lung disease (ILD) is relatively rare and not well characterized (1). MPA is much more common than GPA in Japan with high frequency of interstitial lung disease (1). Objectives: The aim was to analyze clinical and radiographic characteristics of ILD in our patient population with MPA and its impact on survival. Methods: We retrospectively investigated clinical charts in 72 Japanese patients with ANCA-associated vasculitis who admitted to our University hospital from 2006 through 2011. ANCA-associated vasculitis was reclassified according to Watts' classification criteria (2). We analyzed clinical characteristics, survival, and causes of death in patients with MPA. Chest high resolution CT (HRCT) was reviewed by YK, HY, and YY together. Results: Out of the 72 patients, 50 patients (69%) had MPA. Mean age was 70 year-old and mean follow-up period was 31 months in patients with MPA. Thirty-one of 50 patients (62%) were female. Nineteen patients with MPA (38%) had current or past smoking history. Forty-nine patients (98%) had positive for MPO-ANCA. There were no PR3-ANCA positive patients. Out of the 50 MPA patients, 27 (54%), 14 (28%) and 3 (6%) patients had ILD, emphysema and alveolar hemorrhage, respectively. Forty-one patients (82%) had renal involvement. In 27 MPA patients with ILD, chest HRCT revealed ground-glass opacities in 18 (67%), honeycomb in 20 (74%), multiple cystic lesions in 8 (30%) and traction bronchiectasis in 4 (15%).Eight patients (30%) had concomitant emphysema and met the diagnosis of combined pulmonary fibrosis and emphysema (CPFE) (3). Cyclophosphamide was administered in 12 patients, azathioprine in 3, glucocorticoid monotherapy in the rest of 12. After the treatment ILD showed progression in 7 (26%), improvement of ground glass/reticular opacity in 3 (11%) and stabilization in the rest of 17 (63%). Kaplan-Meier survival analysis showed 94% and 70% of survival at 2 and 5 years, respectively. There was no significant difference of survival between MPA patients with and without ILD. Conclusions: ILD was frequently complicated in this cohort of MPA and responded to the treatment for vasculitis in 74% of the cases, suggesting better prognosis than idiopathic pulmonary fibrosis. References: Yamada H. ANCA associated lung fibrosis. Semin Respir Crit Care Med 2011; 32(3): 322-327. Watts R, et al. Development and validation of a consensus methodology for the classification of the ANCA-associated vasculitides and polyarteritis nodosa for epidemiological studies. Ann Rheum Dis 2007;66;222-227. Cottin V, et al. Combined pulmonary fibrosis and emphysema: a distinct underrecognised entity. Eur Respir J. 2005;26:586–93. Disclosure of Interest: None Declared